Efektivitas Terapi Video Directly Observed Therapy (VDOT) Dibandingkan dengan Directly Observed Therapy (DOT) dalam Meningkatkan Kepatuhan Minum Obat pada Pasien TB - Herminia Maria Ximenez; Yuni Sufyanti Arief; Elida Ulfiana; Hasanudin Hasanudin (Journal of Telenursing (JOTING), 2022)
This study aims to assess the effectiveness of Video Directly Observed Therapy (VDOT) compared to Directly Observed Therapy (DOT) in improving medication adherence in TB patients. The method used is a systematic review using the CINAHL, PubMed, and Scopus databases. The results showed that 2 articles discussed routine treatment monitoring for face-to-face DOT at the patient's home or agreed with location during weekdays, and 8 articles discussed DOT by meeting with health department staff at TB clinics (clinic-based DOT. There were 5 articles using VOT intervention by sending videos (asynchronously) using a software application and 6 articles using VDOT conducting live video conferences while taking TB drugs. Keywords: Directly Observed Therapy, Tuberculosis, Video Observed Therapy